Wear-resistant modified PP composite material for cosmetic packaging bottle and preparation method thereof

By modifying nano alumina and nano silica and combining polypropylene, combining materials such as caffeic acid and sodium alginate to form an antioxidant film layer, the problem of oil oxidation and wear during use of cosmetic packaging bottles is solved. , improves its wear resistance and oxidation resistance.

CN119241888AInactive Publication Date: 2025-01-03YUYAO WEIHANG PLASTICS IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411763319.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Cosmetic packaging bottles are prone to failure due to oil oxidation and wear during use, and the wear resistance of existing plastic materials is insufficient, making it difficult to meet the needs of long-term use and frequent use.

Method used

Nanoalumina and nanosilicon dioxide were modified using 3-(2-aminoethylamino)propyltrimethoxysilane, and combined with polypropylene through a stretching rheology extruder to combine caffeic acid and alginic acid. Materials such as sodium and chitosan form an antioxidant film layer, improving the mechanical properties and antioxidant ability of the material.

Benefits of technology

It realizes the high bending strength, tensile strength, impact strength and scratch resistance of cosmetic packaging bottles, and also has good antioxidant properties, extending the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241888A_ABST
    Figure CN119241888A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of plastics, and particularly discloses a modified PP composite material for a wear-resistant cosmetic packaging bottle and a preparation method of the modified PP composite material. According to the modified PP composite material for the wear-resistant cosmetic packaging bottle, 3-(2-aminoethylamino) propyltrimethoxysilane is adopted to modify nano aluminum oxide and nano silicon dioxide, then the modified nano aluminum oxide and nano silicon dioxide, a lubricant and polypropylene are subjected to extrusion and injection molding through an extensional rheology extruder, then the inner surface of the PP bottle is modified through caffeic acid, and the modified PP composite material for the wear-resistant cosmetic packaging bottle is obtained. And then alternately assembling the sodium alginate film and the chitosan film. Finally, the modified PP composite material for the wear-resistant cosmetic packaging bottle is obtained. The prepared modified PP composite material for the wear-resistant cosmetic packaging bottle has the characteristics of high bending strength, high tensile strength, excellent impact strength, good wear resistance and scratch resistance and strong oxidation resistance, and is suitable for cosmetic packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of plastic technology, and more specifically, to a modified PP composite material for wear-resistant cosmetic packaging bottles and a preparation method thereof. Background Art

[0002] There are many types of cosmetics, most of which are in the form of liquids, creams, powders, etc. The packaging materials of cosmetics are mostly made of plastic and glass, with unique and aesthetic designs to highlight the efficacy and performance of cosmetics. The packaging of cosmetics plays an important role in the storage, transportation and promotion and sales of cosmetics brands. Cosmetic packaging materials need to protect cosmetics from moisture and oxidation.

[0003] Plastics are polymer compounds made from monomers through addition polymerization or condensation polymerization. The main component of plastics is resin, and the remaining components are fillers, lubricants, plasticizers and other additives. Most plastics are light, chemically stable, rust-proof, impact-resistant, wear-resistant, insulating, low thermal conductivity, good colorability and low processing cost. Therefore, plastic packaging is often used in the cosmetic packaging field.

[0004] Many cosmetics contain antioxidant ingredients that are beneficial to the skin, but since cosmetics need to be used frequently and for a long time, their oils and other ingredients will gradually be oxidized and destroyed. In addition, since they are used frequently, cosmetic packaging also needs to have excellent wear resistance. Summary of the invention

[0005] In order to further improve the wear resistance and anti-oxidation function of cosmetic packaging bottles, the present application provides a modified PP composite material for wear-resistant cosmetic packaging bottles and a preparation method thereof.

[0006] In the first aspect, the present application provides a technical solution using the following:

[0007] A method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles comprises the following steps: S1, mixing 3-(2-aminoethylamino)propyltrimethoxysilane, methanol and water in proportion, adjusting the pH value to between 3 and 4, stirring for 3 to 4 hours, adding nano-alumina and nano-silicon dioxide, stirring for 5 to 10 minutes at 100 to 110°C, filtering, washing and drying to obtain a nano-filler; S2, mixing and dispersing a lubricant, polypropylene and a nano-filler in a high-speed mixer for 10 to 15 minutes, and then extruding and processing in a stretching rheology extruder, injection molding to obtain a PP bottle material; S3, adding caffeic acid and persulfate to the mixture; Amine and water are mixed, poured into a PP bottle, heated to 70-75°C, ethylenediamine is added, stirred for reaction for 8-12 minutes, then rinsed with deionized water and acetone, and dried to obtain a modified PP bottle material; S4, polyelectrolytes containing chitosan and sodium alginate are prepared respectively, and then the polyelectrolyte containing sodium alginate is contacted with the inner surface of the modified PP bottle material for 4-8 minutes, and then washed with water, and then the polyelectrolyte containing chitosan is contacted with the inner surface of the modified PP bottle material for 4-8 minutes, and then washed with water, and this is a cycle, and the above steps are repeated. After completion, drying is performed to obtain a modified PP composite material for wear-resistant cosmetic packaging bottles.

[0008] By adopting the above technical scheme, 3-(2-aminoethylamino)propyltrimethoxysilane is used to modify nano-alumina and nano-silica, and then extruded and injected with lubricant and polypropylene through a stretching rheological extruder, and then the inner surface of the PP bottle is modified by caffeic acid, and then sodium alginate and chitosan films are alternately assembled. Finally, a modified PP composite material for wear-resistant cosmetic packaging bottles with excellent mechanical properties and antioxidant function is obtained.

[0009] Preferably, the usage ratio of 3-(2-aminoethylamino)propyltrimethoxysilane, methanol, water, nano-alumina and nano-silicon dioxide in S1 is (1-1.5) g: (2.2-3.5) mL: (7.5-12.8) mL: (2-3.6) g: (4-8) g.

[0010] By adopting the above technical scheme, the modification of nano-alumina and nano-silicon dioxide by 3-(2-aminoethylamino)propyltrimethoxysilane is achieved.

[0011] Preferably, the mass ratio of the lubricant, polypropylene and nanofiller is (12-20) g: (80-100): (6-8.5); the lubricant is YY-5031.

[0012] By adopting the above technical scheme, the modified nano-alumina and nano-silicon dioxide are compounded with the lubricant and polypropylene, and the silane coupling agent can be entangled with the polypropylene molecular chain to a certain extent, thereby increasing its strength, reducing the effect of molecular slippage, increasing thermal deformation, and improving wear resistance and scratch resistance.

[0013] Preferably, the extrusion processing parameters of the extensional rheology extruder are: the temperature from the hopper to the die head is 175-185°C, 195-205°C, 215-225°C, and 235-245°C, respectively, and the rotation speed is 20-30rpm.

[0014] By adopting the above technical solution and using the stretching rheological extrusion process, the nano filler can be more evenly distributed in the polypropylene matrix.

[0015] Preferably, the usage ratio of caffeic acid, ammonium persulfate, water and ethylenediamine is (5-8) g: (6.8-10.5) g: (300-400) mL: (1.2-2.4) g.

[0016] By adopting the above technical scheme, caffeic acid polymerizes on the inner surface of the PP bottle in the ammonium persulfate and amino system provided by ethylenediamine and modified filler to form a multi-amino polar environment, thereby improving the non-polar inert characteristics of the inner surface of the PP bottle and providing a good foundation for the subsequent assembly of chitosan and sodium alginate.

[0017] Preferably, the preparation method of the polyelectrolyte containing chitosan is: water, glacial acetic acid and sodium acetate powder are configured into a solution with a pH value of 3.5-4.5, and then chitosan is added to form a solution with a concentration of 2.5-3 g / L.

[0018] The preparation method of the polyelectrolyte containing sodium alginate is as follows: dissolving sodium alginate in deionized water to form a solution with a concentration of 2.5-3 g / L.

[0019] By adopting the above technical solution, the inner surface antioxidant activity of the modified PP composite material for wear-resistant cosmetic packaging bottles prepared at this concentration and pH value is the best.

[0020] Preferably, in S4, the number of cycles is 8-10.

[0021] By adopting the above technical solution, the inner surface antioxidant film layer of the modified PP composite material for wear-resistant cosmetic packaging bottles obtained under this number of cycles is moderate and the activity is maximized.

[0022] In a second aspect, the present application provides a modified PP composite material for wear-resistant cosmetic packaging bottles, which has the best antioxidant activity when prepared by the above method.

[0023] In summary, this application has the following beneficial effects:

[0024] 1. This application uses 3-(2-aminoethylamino)propyltrimethoxysilane to modify nano-alumina and nano-silica, and then extrudes and injects them with lubricants and polypropylene through a stretching rheological extruder, and then modifies the inner surface of the PP bottle with caffeic acid, and then alternately assembles sodium alginate and chitosan films. Finally, a modified PP composite material for wear-resistant cosmetic packaging bottles with excellent mechanical properties and antioxidant function is obtained.

[0025] 2. In the present application, it is preferred to use polyamino 3-(2-aminoethylamino)propyltrimethoxysilane to modify nano-alumina and nano-silicon dioxide, and then use a lubricant as a compatibilizer. Through the tensile rheological extrusion process, the modified nano-filler can be entangled with the polypropylene molecular chain to a certain extent, thereby increasing its strength, reducing the effect of molecular slip, increasing thermal deformation, and improving wear resistance and scratch resistance. Caffeic acid is polymerized on the inner surface of the PP bottle material in an ammonium persulfate and amino system, and then sodium alginate and chitosan are alternately deposited, thereby forming a large number of amino and carboxyl active functional groups on the inner surface, giving it excellent antioxidant ability.

[0026] 3. The modified PP composite material for wear-resistant cosmetic packaging bottles prepared by the preparation method of the present application has the characteristics of high bending strength, high tensile strength, excellent impact strength, good wear and scratch resistance, and strong antioxidant performance, and is particularly suitable for cosmetic packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 : SEM images of the cross-sections of the modified PP composite materials for wear-resistant cosmetic packaging bottles prepared in Example 2, Comparative Example 2 and Comparative Example 3 of the present application, wherein the top one is Comparative Example 3, the middle one is Comparative Example 2, and the bottom one is Comparative Example 1.

[0028] Figure 2 : SEM images of the cross-sectional inner surface of the modified PP composite material for wear-resistant cosmetic packaging bottles prepared in Example 2 of the present application, wherein (a) is the PP bottle material prepared in Example 2, (b) is the modified PP bottle material prepared in Example 2, (c) is the modified PP composite material for wear-resistant cosmetic packaging bottles prepared in Example 2, and (d) is the modified PP composite material for wear-resistant cosmetic packaging bottles prepared in Comparative Example 5. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0031] Example

[0032] Example 1

[0033] A modified PP composite material for wear-resistant cosmetic packaging bottles is prepared by the following steps:

[0034] S1, after mixing 3-(2-aminoethylamino)propyltrimethoxysilane, methanol and water in proportion, adjusting the pH value to 3, stirring for 3-4 hours, adding nano-alumina and nano-silica, stirring for 10 minutes at 100°C, and then filtering, washing and drying to obtain a nano-filler; the amount ratio of 3-(2-aminoethylamino)propyltrimethoxysilane, methanol, water, nano-alumina and nano-silica in S1 is 1g:2.2mL:7.5mL:2g:4g.

[0035] S2, mixing and dispersing the lubricant, polypropylene and nanofiller in a high-speed mixer for 10 minutes, and then extruding and injection molding in an extensional rheological extruder to obtain a PP bottle material; the mass ratio of the lubricant, polypropylene and nanofiller is 12g:80:6; the lubricant is YY-5031 (purchased from Guangzhou Yuantai New Materials Co., Ltd.); the extrusion processing parameters of the extensional rheological extruder are: the temperature from the hopper to the die head is 175°C, 195°C, 215°C, and 235°C, respectively, and the rotation speed is 20rpm.

[0036] S3, mixing caffeic acid, ammonium persulfate and water, pouring into a PP bottle, heating to 70°C, adding ethylenediamine, stirring and reacting for 8 minutes, then washing with deionized water and acetone, and drying to obtain a modified PP bottle material; the amount ratio of caffeic acid, ammonium persulfate, water, and ethylenediamine is 5g:6.8g:300mL:1.2g.

[0037] S4, prepare water, glacial acetic acid and sodium acetate powder into a solution with a pH value of 3.5, then add chitosan to form a solution with a concentration of 2.5 g / L; dissolve sodium alginate in deionized water to form a solution with a concentration of 2.5 g / L; then contact the polyelectrolyte containing sodium alginate with the inner surface of the modified PP bottle material for 4 minutes, and then wash with water, then contact the polyelectrolyte containing chitosan with the inner surface of the modified PP bottle material for 4 minutes, and then wash with water, and repeat the above steps for 8 cycles, dry, and obtain a modified PP composite material for wear-resistant cosmetic packaging bottles.

[0038] Example 2

[0039] A modified PP composite material for wear-resistant cosmetic packaging bottles is prepared by the following steps:

[0040] S1, after mixing 3-(2-aminoethylamino)propyltrimethoxysilane, methanol and water in proportion, adjusting the pH value to between 3.5, stirring for 3.5 hours, adding nano-alumina and nano-silica, stirring at 1105°C for 8 minutes, and then filtering, washing and drying to obtain a nano-filler; the amount ratio of 3-(2-aminoethylamino)propyltrimethoxysilane, methanol, water, nano-alumina and nano-silica in S1 is 1.2g:2.8mL:10.2mL:3.0g:6g.

[0041] S2, the lubricant, polypropylene and nanofiller are mixed and dispersed in a high-speed mixer for 12 minutes, and then extruded and injection molded in an extensional rheological extruder to obtain a PP bottle material; the mass ratio of the lubricant, polypropylene and nanofiller is 16g:90:7.2; the lubricant is YY-5031 (purchased from Guangzhou Yuantai New Materials Co., Ltd.); the extrusion processing parameters of the extensional rheological extruder are: the temperature from the hopper to the die head is 180°C, 200°C, 220°C, and 240°C, respectively, and the rotation speed is 25rpm.

[0042] S3, mixing caffeic acid, ammonium persulfate and water, pouring into a PP bottle, heating to 72°C, adding ethylenediamine, stirring for 10 minutes, then washing with deionized water and acetone, and drying to obtain a modified PP bottle material; the amount ratio of caffeic acid, ammonium persulfate, water, and ethylenediamine is 7g:8g:350mL:1.8g.

[0043] S4, prepare water, glacial acetic acid and sodium acetate powder into a solution with a pH value of 4, then add chitosan to form a solution with a concentration of 2.8 g / L; dissolve sodium alginate in deionized water to form a solution with a concentration of 2.8 g / L; then contact the polyelectrolyte containing sodium alginate with the inner surface of the modified PP bottle material for 6 minutes, and then wash with water, then contact the polyelectrolyte containing chitosan with the inner surface of the modified PP bottle material for 6 minutes, and then wash with water, and repeat the above steps for 9 cycles, dry, and obtain a modified PP composite material for wear-resistant cosmetic packaging bottles.

[0044] Example 3

[0045] A modified PP composite material for wear-resistant cosmetic packaging bottles is prepared by the following steps:

[0046] S1, after mixing 3-(2-aminoethylamino)propyltrimethoxysilane, methanol and water in proportion, adjusting the pH value to between 4, stirring for 4 hours, adding nano-alumina and nano-silica, stirring at 110°C for 10 minutes, and then filtering, washing and drying to obtain a nano-filler; the amount ratio of 3-(2-aminoethylamino)propyltrimethoxysilane, methanol, water, nano-alumina and nano-silica in S1 is 1.5g:3.5mL:12.8mL:3.6g:8g.

[0047] S2, mixing and dispersing the lubricant, polypropylene and nanofiller in a high-speed mixer for 15 minutes, and then extruding and injection molding in an extensional rheological extruder to obtain a PP bottle material; the mass ratio of the lubricant, polypropylene and nanofiller is 20g:100:8.5; the lubricant is YY-5031 (purchased from Guangzhou Yuantai New Materials Co., Ltd.); the extrusion processing parameters of the extensional rheological extruder are: the temperature from the hopper to the die head is 185°C, 205°C, 225°C, and 245°C, respectively, and the rotation speed is 30rpm.

[0048] S3, mix caffeic acid, ammonium persulfate and water, pour into a PP bottle, heat to 75°C, add ethylenediamine, stir and react for 12 minutes, then rinse with deionized water and acetone, and dry to obtain a modified PP bottle material; the amount ratio of caffeic acid, ammonium persulfate, water and ethylenediamine is 8g:10.5g:400mL:2.4g.

[0049] S4, prepare water, glacial acetic acid and sodium acetate powder into a solution with a pH value of 4.5, then add chitosan to form a solution with a concentration of 3 g / L; dissolve sodium alginate in deionized water to form a solution with a concentration of 3 g / L; then contact the polyelectrolyte containing sodium alginate with the inner surface of the modified PP bottle material for 8 minutes, and then wash with water, then contact the polyelectrolyte containing chitosan with the inner surface of the modified PP bottle material for 8 minutes, and then wash with water, and repeat the above steps for 10 cycles, dry, and obtain a modified PP composite material for wear-resistant cosmetic packaging bottles.

[0050] Comparative Example 1

[0051] The same as Example 2, except that the nano-alumina is replaced by nano-silicon dioxide.

[0052] Comparative Example 2

[0053] The same as Example 2, except that "3-(2-aminoethylamino)propyltrimethoxysilane" is replaced by "octyltrimethoxysilane".

[0054] Comparative Example 3

[0055] Same as Example 2, except that the "extensional rheology extruder" is replaced by a "twin-screw extruder".

[0056] Comparative Example 4

[0057] The same as Example 2, except that "caffeic acid" is replaced by "gallic acid".

[0058] Comparative Example 5

[0059] The same as Example 2, except that the number of cycles is set to 15 times.

[0060] Performance testing

[0061] The outer morphology of the brittle fracture surface of the modified PP composite material for wear-resistant cosmetic packaging bottles prepared in Example 2, Comparative Example 2 and Comparative Example 3 was analyzed by scanning electron microscope. The results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the brittle section of the modified PP composite material for wear-resistant cosmetic packaging bottles prepared in comparative example 3 of the present application is relatively flat, indicating that it is very easy to produce concentrated stress during the impact process, resulting in reduced toughness; the brittle section of the modified PP composite material for wear-resistant cosmetic packaging bottles prepared using nanofillers modified with octyltrimethoxysilane in comparative example 2 is relatively poor in flatness, indicating that there is tensile stress around its section, and the stress generated during the impact process is largely transferred to the outside of the crack, and the impact stress is significantly dispersed, and the toughness is strong. The brittle section of the modified PP composite material for wear-resistant cosmetic packaging bottles in Example 2 is the most uneven, indicating that the nanofiller modified by 3-(2-aminoethylamino)propyltrimethoxysilane is closely entangled with the polypropylene matrix, and the de-entanglement behavior during the impact process will absorb the impact stress, and its toughness is the strongest.

[0062] The PP bottle material, modified PP bottle material, modified PP composite material for wear-resistant cosmetic packaging bottle prepared in Example 2 and modified PP composite material for wear-resistant cosmetic packaging bottle prepared in Comparative Example 5 were subjected to scanning electron microscopy analysis of the inner side morphology of the cross section. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the inner surface of the PP bottle material prepared in Example 2 is relatively smooth and flat, while the inner surface of the modified PP bottle material is a foam-like grafted layer, and the grafted layer is in close contact with the substrate; the inner surface of the modified PP composite material for wear-resistant cosmetic packaging bottles prepared in Example 2 becomes relatively flat compared with the modified PP bottle material, and the surface has an obvious layered structure, and the inner surface of the modified PP composite material for wear-resistant cosmetic packaging bottles prepared in Comparative Example 5 is a cross-fiber mesh structure.

[0063] The modified PP composite materials for wear-resistant cosmetic packaging bottles prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to tensile strength test (GB / T 1040.2-2022), bending strength test (ISO 178:2001), impact strength test (ISO 180:2000), scratch resistance test (using a scratch pen to scratch the outer surface 4 cm 2 The scratches are 4mm apart, the scratch interval is 4mm, the scratch pen pressure is 8N, the color difference at the scratches is tested using a colorimeter, the color of the scratches and the complete surface is tested under the Lab model, and the change in color depth (ΔL) is used as a means of characterizing the scratch resistance. The larger the ΔL, the worse the scratch resistance), wear resistance test (GISO 9352-2012), and heat deformation temperature test (GB / T1634.2—2019) are tested. The results are shown in Table 1:

[0064] Table 1. Mechanical properties test

[0065] Tensile strength (MPa) Bending strength (MPa) <![CDATA[Impact strength (kJ / m 2 )]]> Scratch resistance (ΔL) Wear rate (%) Heat deformation temperature (℃) Example 1 22.3 1235.4 18.6 1.56 2.35 72.5 Example 2 23.8 1345.2 18.1 1.48 2.31 72.9 Example 3 21.9 1312.7 19.3 1.45 2.27 73.1 Comparative Example 1 22.5 1308.6 17.5 1.65 2.41 70.2 Comparative Example 2 18.7 1123.5 15.2 1.71 2.45 68.5 Comparative Example 3 16.4 972.8 13.1 1.82 2.51 63.4 Comparative Example 4 23.5 1332.4 18.0 1.49 2.31 71.7 Comparative Example 5 23.1 1321.6 17.8 1.48 2.32 70.3

[0066] It can be seen from Table 1 that the modified PP composite materials for wear-resistant cosmetic packaging bottles prepared in Examples 1 to 3 of the present application have the characteristics of high bending strength, high tensile strength, excellent impact strength, and good wear and scratch resistance. Combined with Comparative Examples 1 to 5, it can be seen that 3-(2-aminoethylamino)propyltrimethoxysilane and the extensional rheology extruder have a greater influence on its comprehensive performance, and the mixed addition of nano-alumina and nano-silicon dioxide can improve its wear and scratch resistance.

[0067] Antioxidant performance test:

[0068] 200 mL of olive oil, 12 mL of Tween 20 and 300 mL of ethanol were mixed and homogenized for 10 min using a high-speed dispersing homogenizer to obtain a water-oil emulsion. The prepared water-oil emulsion was added in equal amounts to the PP bottle material (recorded as Group A), the modified PP bottle material (recorded as Group B), the modified PP composite material for wear-resistant cosmetic packaging bottles (recorded as Group C), Comparative Example 2 (recorded as Group D), Comparative Example 4 (recorded as Group E) and the prepared Comparative Example 5 (recorded as Group F). The modified PP composite material for wear-resistant cosmetic packaging bottles was prepared. The same amount of two water-oil emulsions were added to two glass bottles, one of which contained disodium ethylenediaminetetraacetate (0.25 g of disodium ethylenediaminetetraacetate per 1 kg of water-oil emulsion) (recorded as Group G), and the other was recorded as Group H. After the water-oil emulsions were shaken at 35°C for 21 days, the conjugated diene value and hexanal content of the water-oil emulsions were tested, and the conjugated diene value and hexanal content of Group H before the experiment were tested. The results are shown in Table 2:

[0069] Table 2. Antioxidant performance test

[0070] Conjugated diene value n-Hexanal content (mg / L) Group A 7.68 7.958 Group B 4.13 0.416 Group C 3.77 0.324 Group D 4.08 0.397 Group E 3.95 0.458 Group F 4.56 0.373 Group G 3.28 0.361 Group H 7.35 7.132 Before the experiment in group H 1.52 0.081

[0071] It can be seen from Table 2 that the modified PP composite material for wear-resistant cosmetic packaging bottles prepared in Example 2 of the present application has the best antioxidant performance.

[0072] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, a person skilled in the art may make non-creative modifications to the present embodiment as needed, and such modifications shall be protected by the patent law as long as they are within the scope of protection claimed in the present application.

Claims

1. A method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles, characterized in that: The method comprises the following steps: S1, mixing 3-(2-aminoethylamino)propyltrimethoxysilane, methanol and water in proportion, adjusting the pH value to between 3 and 4, stirring for 3 to 4 hours, adding nano-alumina and nano-silicon dioxide, stirring for 5 to 10 minutes at 100 to 110°C, filtering, washing and drying to obtain nano-fillers; S2, mixing and dispersing lubricant, polypropylene and nano-fillers in a high-speed mixer for 10 to 15 minutes, and then extruding and injection molding in a stretching rheology extruder to obtain PP bottle materials; S3, mixing caffeic acid, ammonium persulfate and water, and pouring the mixture into a PP bottle; In step S4, the temperature is raised to 70-75°C, ethylenediamine is added, the reaction is stirred for 8-12 minutes, and then the mixture is rinsed with deionized water and acetone, and dried to obtain a modified PP bottle material; S5, polyelectrolytes containing chitosan and sodium alginate are prepared respectively, and then the polyelectrolyte containing sodium alginate is contacted with the inner surface of the modified PP bottle material for 4-8 minutes, and then washed with water, and then the polyelectrolyte containing chitosan is contacted with the inner surface of the modified PP bottle material for 4-8 minutes, and then washed with water, as a cycle, the above steps are repeated, and after completion, the modified PP composite material for wear-resistant cosmetic packaging bottles is obtained by drying.

2. The method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles according to claim 1, characterized in that: The usage ratio of 3-(2-aminoethylamino)propyltrimethoxysilane, methanol, water, nano-alumina and nano-silicon dioxide in S1 is (1-1.5) g: (2.2-3.5) mL: (7.5-12.8) mL: (2-3.6) g: (4-8) g.

3. The method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles according to claim 2, characterized in that: The mass ratio of the lubricant, polypropylene and nanofiller is (12-20) g: (80-100): (6-8.5); the lubricant is YY-5031.

4. The method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles according to claim 3, characterized in that: The extrusion processing parameters of the extensional rheology extruder are as follows: the temperature from the hopper to the die head is 175-185° C., 195-205° C., 215-225° C., and 235-245° C., respectively, and the rotation speed is 20-30 rpm.

5. The method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles according to claim 4, characterized in that: The dosage ratio of the caffeic acid, ammonium persulfate, water and ethylenediamine is (5-8) g: (6.8-10.5) g: (300-400) mL: (1.2-2.4) g.

6. The method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles according to claim 5, characterized in that: The preparation method of the polyelectrolyte containing chitosan is as follows: water, glacial acetic acid and sodium acetate powder are configured into a solution with a pH value of 3.5-4.5, and then chitosan is added to form a solution with a concentration of 2.5-3 g / L.

7. The method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles according to claim 6, characterized in that: The preparation method of the polyelectrolyte containing sodium alginate is as follows: sodium alginate is dissolved in deionized water to form a solution with a concentration of 2.5-3 g / L.

8. The method for preparing a modified PP composite material for wear-resistant cosmetic packaging bottles according to claim 7, wherein in S4, the number of cycles is 8-10.

9. A modified PP composite material for wear-resistant cosmetic packaging bottles, characterized in that: The modified PP composite material for wear-resistant cosmetic packaging bottles is prepared by the preparation method of any one of claims 1-8.

Citation Information

Patent Citations

  • Universal method for fast bionic surface functional modification of mussel

    CN107345366A

  • High-transparency PP composite material for lip gloss bottle and preparation method

    CN109575444A

  • Manufacturing process of wear-resistant cosmetic packaging bottle

    CN113388304A

  • Method for carrying out transparent modification on polypropylene through DBS-like transparent modified polypropylene macromolecular nucleating agent

    CN117285778A

  • High-strength wear-resistant PP material and preparation method thereof

    CN118459893A